Interface strategies in monolingual and end-state L2 Spanish grammars are not that different - Parafita Couto, María C.; Mueller Gathercole, Virginia C.; Stadthagen-González, Hans (Frontiers in Psychology, 2015)
This study explores syntactic, pragmatic, and lexical influences on adherence to SV and VS orders in native and fluent L2 speakers of Spanish. A judgment task examined 20 native monolingual and 20 longstanding L2 bilingual Spanish speakers’ acceptance of SV and VS structures. Seventy-six distinct verbs were tested under a combination of syntactic and pragmatic constraints. Our findings challenge the hypothesis that internal interfaces are acquired more easily than external interfaces (Sorace, 2005, 2011; Sorace & Filiaci, 2006; White 2006). Additional findings are that (a) bilinguals' judgments are less firm overall than monolinguals' (i.e., monolinguals are more likely to give extreme "yes" or "no" judgments) and (b) individual verbs do not necessarily behave as predicted under standard definitions of unaccusatives and unergatives. Correlations of the patterns found in the data with verb frequencies suggest that usage-based accounts of grammatical knowledge could help provide insight into speakers' knowledge of these constructs.